Slip velocity dependence of friction-permeability response of shale fractures - Jia, Yunzhong (2022)
Fluid injection-induced fracture slip during hydraulic stimulation of shales may be seismic or aseismic with the slip mode potentially influencing the evolution of permeability and subsequent shale gas production. We report a series of friction-permeability tests with constant and stepped velocities on planar saw-cut fractures of Longmaxi shale, Green River shale and Marcellus shale. In particular we explore the additive effect of stepped velocity on fracture permeability evolution relative to the background permeability driven at constant velocity. Fracture permeability decreases at larger slip displacement at constant velocity presumably due to asperity degradation and clay swelling. Sudden up-steps in slip velocity temporarily enhance fracture permeability as a result of shear dilation on hard minerals, but permeability net decreases with increasing slip displacement as wear products fill the pore space. Fracture surface roughness is the link between the fracture permeability and friction coefficient, which are both influenced by mineralogical composition. The fractures and sheared-off particles in the tectosilicate-rich and carbonate-rich shales dilate to increase fracture permeability, whereas asperity comminution readily occurs in the phyllosilicate-rich shale to reduce fracture permeability. The results potentially improve our ability to facilitate shale gas extraction and to mitigate the associated seismic risks.